The Effect of Implementation of Professional Development, Organizational Climate, and Teacher Commitments on the Performance of Junior High School Teachers - Putri, Abida Ferindistika; Maisyaroh, Maisyaroh; Supriyanto, Achmad; Sultoni, Sultoni (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2021)
Abstract: The purpose of this study was to determine the implementation of professional coaching, organizational climate, commitment, and teacher performance in junior high schools, the effect of implementing professional coaching, organizational climate, and commitment to teacher performance in junior high schools. This study uses a quantitative approach. The population is 2,028 people with a sample of 334 people. The instrument in this study was in the form of a closed questionnaire using a Likert scale. Collecting data through the distribution of questionnaires to the respondents of SMPN teachers in Tulungagung Regency. Descriptive data analysis and multiple regression. The conclusions of this study indicate that: (1) the implementation of professional development, organizational climate, teacher commitment, and teacher performance in junior high schools are in the very high category, and (2) there is a simultaneous or partial influence on the variables of the implementation of professional coaching, organizational climate. , and commitment to teacher performance in junior secondary schools. Keywords: professional coaching; organizational climate; teacher commitment; teacher performance